2017
DOI: 10.1021/acs.energyfuels.6b02161
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Asphaltene Aggregation through Molecular Dynamics: Insights and Limitations

Abstract: We report classical atomistic molecular dynamics simulations of four structurally diverse model asphaltenes, a model resin, and their respective mixtures in toluene or heptane under ambient conditions. Relatively large systems (∼50 000 atoms) and long time scales (>80 ns) are explored. Wherever possible, comparisons are made to available experimental observations asserting the validity of the models. When the asphaltenes are dissolved in toluene, a continuous distribution of cluster sizes is observed with aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
291
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(312 citation statements)
references
References 90 publications
20
291
1
Order By: Relevance
“…These findings indicate that aggregation among individual asphaltene molecules is primarily driven by π − π interactions, in a hierarchical way. Oppositely, experimental (Varadaraj and Brons 2012;Schulze et al 2015;Subramanian et al 2017) as well as simulation-based evidence (Headen et al 2009(Headen et al , 2017 exist corroborating the supramolecular, Gray's model. These works showed that asphaltene self-interaction depends also on acid-base and polar interactions.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…These findings indicate that aggregation among individual asphaltene molecules is primarily driven by π − π interactions, in a hierarchical way. Oppositely, experimental (Varadaraj and Brons 2012;Schulze et al 2015;Subramanian et al 2017) as well as simulation-based evidence (Headen et al 2009(Headen et al , 2017 exist corroborating the supramolecular, Gray's model. These works showed that asphaltene self-interaction depends also on acid-base and polar interactions.…”
Section: Introductionmentioning
confidence: 62%
“…They can also be responsible for coke deposits, catalysis deactivation, low yield in fuels or chemicals, significant content of sulfur or metals in the output and energy consumption during the upgrading process (Merdrignac and Espinat 2007). Both the chemical composition and the molecular cartography (i.e, how the chemical elements form the various structures) play a key role in the understanding of this problematic phenomenon (Headen et al 2017). In this way, a clear and well-determined structure-function link between molecular structure and aggregation behavior of asphaltenes is highly sought after so that these nasty effects can be avoided, and new refining techniques, asphaltene inhibitors and catalysts can be developed, and so on (Murgich et al 1996;Takanohashi et al 2003;Ortega-Rodriguez et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These structures have been previously studied extensively by atomistic simulation 1,11,27 respectively. These structures have a very similar atomic composition to that obtained from the elemental analysis of the asphaltene sample used in this study, as shown in Table 1.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The direct comparison of simulated and experimental structures provides novel insight into the extent to which existing simulation strategies successfully predict asphaltene structures and provides pathways for additional study and improvement. Herein we present a preliminary simulation study of three types of asphaltene molecular structures as used in our previous works 26,27 . The structures used have been chosen to exemplify the range of molecular architecture and functionalities present within asphaltenes.…”
mentioning
confidence: 99%
“…Asphaltenes are prone to aggregation that is driven by changes in condition, such as pressure, temperature or compositional changes by blending/incorporating with other elements such as other incompatible oils or gases. [16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%